Aplikasi Peringatan Dini Kebocoran Gas LPG untuk Rumah Tangga dengan Modul NodeMCU ESP32 - Tanumihardja, Wilbert Josef; Dasawati, Elis Sondang (Jurnal Informatika dan Bisnis, 2024)
The development of technology is very rapid, starting from computers that can only perform mathematical calculations, to various smart devices that have become an integral part of everyday life. This development has brought many good benefits to human life. One example is the existence of early warning technology for disasters. Early warning is a very important element in risk management efforts." With early warning of disasters, people can provide appropriate responses to save themselves, avoid casualties, and reduce the impact of the disaster. This research is field research (Qualitative Method) that uses unstructured interviews, observation, literature study, and documentation. As a data collection technique, this unstructured interview is from the family and from LPG gas users. The system development method uses the Extreme Programming method, and the measurement technique uses data issued by PT Pertamina (Persero) and other literature sources. Early warning alarm system to detect LPG gas leaks for households using the NodeMCU ESP32 module, so as to provide information on the occurrence of LPG gas leaks through LED indicators, buzzers and information on Android-based applications, so that people can take the first handling action. This research is in the form of making an early warning system to detect LPG gas leaks for households using the ESP32 module to detect LPG gas leaks in households to take the first action against LPG gas leaks.